Graduate feedback on a teacher education program and school district support: An argument for a continuum of professional learning. (December 2021) - MacMath, Sheryl; Sivia, Awneet; Britton, Vandy
Highlights: Teacher induction needs to be seen as part of an ongoing process of professional learning. Mentorship programs need to be recognized as a part of teacher induction not an equivalent. School principals, teachers, and school districts have a role to play in teacher induction. Abstract: This phenomenological study aimed to explore how early career teachers were supported in their transition from teacher education to professional practice. It involved interviewing seven recent graduates from a post-degree teacher education program on their perceptions of both the program and their local school district in supporting them as early career teachers. Results involve numerous recommendations for supporting these teachers during their induction into the profession leading to the articulation of a continuum of lifelong professional learning that includes teacher education, induction and mentorship, and professional development. Key responsibilities for school districts, principals, and teacher education faculty are included.